Lymphocyte Migration Inhibition Response in Trichuris muris Infected and Vaccinated Mice - S Gaherwal; MM Prakash (Iranian Journal of Parasitology, 2011)
Background: Immunological response of host and parasite play a key role in developing vaccination and immunization. The present study deals with the immune response and effecter mechanism, which was confirmed by migration inhibition factor (MIF).